EFFECT OF DRYING BY ELECTRIC OVEN ON VIABILITY OF Lactobacillus plantarum AND Bifidobacterium breve - Alzobaay, Amer H.; Abdul Al-Wahid, Rawa' M.; Gazi, Taif J. (Diyala Agricultural Sciences Journal, 2020)
Reconstituted skim milk was used in 12, 20, 25% to cultivate Lactobacillus plantarum and Bifidobacterium breve in 37°C for 24-48 hours after individually inoculation with 10% of bacteria. 20% of reconstitution was chosen for highest growth rate of bacteria among them, the logarithmic numbers of bacteria are 9.75 and 9.85 for Lb. plantarum and Bifi. breve respectively, whereas titratable acidity of milk was 0.67 and 0.65 % respectively, pH values of the 20% were 4.8 and 4.9 respectively7 Cultured Lb. plantarum and Bifi. breve bacteria were dried by using electric oven with or without protectants (10% sterilized dry skim milk). The drying was affected on viability of lactic acid bacteria, drying in electric oven gave the best results when protectants material was added, logarithmic viable numbers were 8.66 and 8.76 for Lb. plantarum and Bifi. breve respectively, followed by, Logarithmic viable count of dried cultures in electric oven before adding the protectants were 8.53 and 8.56 respectively. Moisture content were 4.47 and 4.45 % respectively for Lb. plantarum and Bifi. breve in dried cultures by using electric oven with protectants, while that were (4.65 and 4.63) % respectively in dried cultures by electric oven without protectants.